Front Cover: Intermolecular Photoredox Coupling: Alternative to Norrish Type II Reaction and Yang Cyclization in Ketones with γ‐C−H Bonds (26/2021). Issue 26 (24th June 2021) - Hoffmann, Heiko; Tausch, Michael W.
Abstract : The Front Cover shows the revisited photochemistry of butyrophenone. The bright sun and beautiful nature are symbolizing the photons as clean energy source. After excitation, pathways to wander downhill are standing for different deactivation route which the system can undergo. A new reaction pathway is reported. In addition to the Norrish type II fragmentation and Yang cyclization, intermolecular species are generated: 1, 2‐Dibenzoylethane and pinacols. They account for approx. 20% of the converted starting material, similar to the Yang product. The authors would like to thank the Provadis School (Frankfurt, emblem shown right) for making this work possible. More information can be found in the Communication by H. Hoffmann and M. W. Tausch.